2019
DOI: 10.1002/jsfa.9576
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultra‐performance liquid chromatography–tandem mass spectrometry on sweet cherries to determine phenolic compounds in peel and flesh

Abstract: BACKGOUND Sweet cherries (Prunus avium L.) are rich in polyphenols and have high antioxidant potential. This study deals with the use of ultra‐performance liquid chromatography–tandem mass spectrometry on five cherry cultivars, namely Caihong, Sunburst, Summit, 23–51 and Valeri, to determine the free, conjugated and bound phenolics in peel and flesh. RESULTS Phenolics varied widely based on cherry cultivars and edible parts. Valeri showed the highest phenolics in peel, while the flesh of 23–51 contained a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…The highest subtotal levels of bound phenolics were found in Hongyang (1.16 mg kg −1 FW), whereas the lowest concentration of bound phenolics was found in Xixuan (0.19 mg kg −1 FW). Like the conjugated fractions, caffeic acid was the predominant bound form in kiwifruits, which also was in accordance with the study reported in cherries 17 . Bound phenolics comprise a large proportion in many cereals (such as corn, wheat and rice), but the number is relative low in many fruits 16,34 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The highest subtotal levels of bound phenolics were found in Hongyang (1.16 mg kg −1 FW), whereas the lowest concentration of bound phenolics was found in Xixuan (0.19 mg kg −1 FW). Like the conjugated fractions, caffeic acid was the predominant bound form in kiwifruits, which also was in accordance with the study reported in cherries 17 . Bound phenolics comprise a large proportion in many cereals (such as corn, wheat and rice), but the number is relative low in many fruits 16,34 .…”
Section: Resultssupporting
confidence: 90%
“…Soluble‐free, soluble‐conjugated, and insoluble‐bound phenolics of kiwifruits were isolated following the method of our previously published study, with minor modifications 17 . Briefly, 5 g of kiwifruit was mixed with 20 mL of 80% acidified methanol (0.1% HCl, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Flavonoid extracts were performed according to the method of Gao et al [ 65 ] with some modifications. Two grams of the freeze-dried powder of plum flesh was extracted with 30 mL of 80% methanol in the dark for 24 h at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic and flavonoid analyses were performed as described previously by Gao et al . [ 65 ]. The samples were analysed by using an Acquity UPLC system (Waters, Milford, MA) with a triple quadrupole mass spectrometer (TQ-S, Waters Micromass, Manchester, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation